Different polymethylmethacrylate (PMMA) reinforcement strategies for long bone osteoplasty procedures: a controlled laboratory comparison using the 4-point bending test - David Putzer; Valentina Egger; Johannes Pallua; Martin Thaler; Werner Schmölz; Michael Nogler (BMC Musculoskeletal Disorders)
Abstract Background Cementoplasty has been successfully used for treating fractures in various parts of the human body, although the use in weight-bearing long bones is a subject of controversial debate. Strategies to improve the mechanical properties of polymethylmethacrylate-based bone cement (BC) comprise changing the chemical composition or the application of metal reinforcement strategies. In clinical practice reinforced bone cement is used despite biomechanical basic research regarding this topic being scare. Objective The aim of the present study was to evaluate the biomechanical properties of two different reinforcement strategies against non-reinforced polymethylmethacrylate-based BC subjected to bending stress. Methods In this controlled comparative laboratory analysis, we evaluated two types of reinforcement strategies in comparison to a control group (C). BC was reinforced with a Kirschner wire (group CW) or with a prestressed twinned steel cable (group CC); control group C was native polymethylmethacrylate-based BC. All the samples were prepared using a custom-made mould and underwent 4-point bending stress until fracture using a testing machine. Flexural strength, maximum strain, and Young’s modulus were assessed for the three groups and compared using the Kruskal‒Wallis test. Results The mean flexural strength in MPa was 48 ± 12 in C, 64 ± 6 in CW, and 63 ± 14 in CC. A significantly greater flexural strength of + 33% was found in both reinforced groups than in the C group (C vs. CW p = 0.011, C vs. CC p = 0.023). Regarding the flexural strength, no statistically significant difference could be found between the two reinforcement strategies CW and CC (p = 0.957). The maximum strain was 3.0% in C and CW and 3.8% in CC and no difference between the three groups was observed (p = 0.087). The Young’s modulus in GPa was 2.7 for C, 2.8 for CW, and 2.4 for CC. The comparison of Young’s module using the Kruskal-Wallis test showed no statistically significant difference between CC, CW and C (p = 0.051). Conclusions We detected an improvement in flexural strength in the reinforced groups. Both reinforcement through K-wire and prestressed cables promoted increased flexural strength. Furthermore, less material failure was observed with possible realignment and subsequent residual stability despite bone cement fracture. From a biomechanical view, the concept of macro metal reinforcement of osteoplasty is viable.